The Effect of Problem Based Learning Model (PBL) on Students' Level of Understanding of Mathematical Concepts at Madrasah Aliyah Negeri - Siskawati, Fury Styo (Universitas Islam Jember, 2016)
This study aims to determine the effect of problem-based learning models on students' level of understanding of mathematical concepts. The sample in this study were students of class XI MAN Jember 1. The results showed that the level of understanding of the mathematical concepts of students taught by problem-based learning models was higher than students taught by the lecture method. By consulting the value of F count 4.788859655 and F table 3.99 then F count> F table there is an influence. The level of understanding of students' mathematical concepts taught by the Problem Based Learning Model and Lecture Method is not related to initial achievement. By consulting the value of F count 0.092804855 and F table 3.14, then F count <F table there is no effect. There is no interaction between the use of Problem Based Learning Model and Lecture Method and student achievement. By consulting the value of F count 1.038540086 and F table 3.14, then F count <F table there is no effect. So it can be concluded that the problem-based learning model is suitable for use in mathematics learning and can increase achievement, activity and creativity. In addition, this learning model is suitable for students with various levels of achievement, not only students with certain achievements. So that the problem-based learning model can be used as one of the preferred learning models that can be applied in schools Keywords: PBL, level of understanding